COMPANY PERFORMANCE MEDIATES THE EFFECT OF ENVIRONMENTAL PERFORMANCE ON FIRM VALUE - Ilvia Azhari Salsabila; Endah Susilowati (Yayasan Education and Social Center, 2023)
Firm value is a public view of the company based on the reciprocity that the company can provide to stakeholders. This quantitative research raises the object of environmental performance as an independent variable and firm value as the dependent variable and is complemented by company performance as an intervening variable. The purpose of this study is to examine company performance in mediating the effect of environmental performance on firm value. The population in this study are manufacturing companies in the fast moving consumer goods sector listed on the Indonesia Stock Exchange, which recorded 77 companies. Data collection is carried out secondarily which is obtained from the official IDX website and MENLHK PROPER. The research sample was selected using purposive sampling method where there are certain criteria, such as: publishing annual reports during the 2017-2022 period and participating in the PROPER program in the 2017-2022 period. The number of samples in this study amounted to 26 companies. This research analysis uses the PLS test tool (Partial Least Square (PLS) with SmartPLS 4.0 software. The results showed that company performance was able to mediate the effect of environmental performance on firm value. This research is expected to be used as a new reference for further researchers related to existing topics and is expected to be able to be used as a consideration for companies to further improve their environmental performance